Q: -6x plus 72 equals x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x + 10 = 72 6x = 72 - 10 x = 62/6 x = 10.3333

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

(x + 12)(x - 6) = 0 x = 6 or -12

5x + x - 6x + 2x = 2x

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

Related questions

6x + 10 = 72 6x = 72 - 10 x = 62/6 x = 10.3333

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0

(x + 12)(x - 6) = 0 x = 6 or -12

6x+x = 7x

x squared x2

5x + x - 6x + 2x = 2x

6x

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

Using the quadratic equation formula the value of x is -8 or 5

If: 9x+7 = 6x+25 Then: x = 6

x=10